EFEKTIVITAS PARA PELAKU USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DALAM MEMBANGUN PERTUMBUHAN EKONOMI - Silvia Aluf; Syakila Az-Zahwa Nurfatiha; Apriliantoni, Apriliantoni (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This journal discusses the effectiveness of Micro, Small and Medium Enterprises (MSMEs) in supporting Indonesia's economic growth. MSMEs play an important role as the main driver in creating jobs, absorbing labor, and contributing to Gross Domestic Product (GDP), with a contribution reaching 61% in 2023. Fluctuating economic growth in Indonesia is influenced by various factors, both economic and non-economic. economy. Although MSMEs show significant resilience in facing challenges, they still face obstacles such as access to capital, management skills and technology. Through qualitative descriptive analysis, this research highlights the strategic role of MSMEs in economic equality, improving community welfare, and contributing to the country's foreign exchange. The research results show that the effectiveness of MSMEs not only improves individual welfare but also contributes to the stability and growth of the national economy as a whole.